Full Seismic Waveform Modelling and Inversion - Fichtner, Andreas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
Recent progress in numerical methods and computer science allows us today to simulate the propagation of seismic waves through realistically heterogeneous Earth models with unprecedented accuracy. Full waveform tomography is a tomographic technique that takes advantage of numerical solutions of the elastic wave equation. The accuracy of the numerical solutions and the exploitation of complete waveform information result in tomographic images that are both more realistic and better resolved. This book develops and describes state of the art methodologies covering all aspects of full waveform tomography including methods for the numerical solution of the elastic wave equation, the adjoint method, the design of objective functionals and optimisation schemes. It provides a variety of case studies on all scales from local to global based on a large number of examples involving real data. It is a comprehensive reference on full waveform tomography for advanced students, researchers and professionals.
Introduction -- Numerical Solution of the Elastic Wave Equation -- Computing Sensitivity Kernels -- Seismological Data Functionals and their Associated Adjoint Sources -- Iterative Optimisation -- Full Waveform Tomography for Upper-mantle Structure in Australasian Region -- A Comparative Study of Local-scale full Waveform Tomographies -- Source Staking and Data Reduction in Global full Waveform Tomography.
Keywords: Geography; Physical geography; Mathematical geography; Mathematics; Earth Sciences; Geophysics/Geodesy.; Geophysics and Environmental Physics; Applications of Mathematics; Mathematical Applications in Earth Sciences